Growth still is good for the poor - David Dollar; Tatjana Kleineberg; Aart Kraay (Luxembourg Income Study (LIS), 2013)
Incomes in the poorest two quintiles on average increase at the same rate as overall average incomes. This is because, in a global dataset spanning 118 countries over the past four decades, changes in the share of income of the poorest quintiles are generally small and uncorrelated with changes in average income. The variation in changes in quintile shares is also small relative to the variation in growth in average incomes, implying that the latter accounts for most of the variation in income growth in the poorest quintiles. These findings hold across most regions and time periods and when conditioning on a variety of country-level factors that may matter for growth and inequality changes. This evidence confirms the central importance of economic growth for poverty reduction and illustrates the difficulty of identifying specific macroeconomic policies that are significantly associated with the relative growth rates of those in the poorest quintiles.
Keywords: O4; O11; I3; 330; growth; inequality